Les Bienveillantes de Jonathan Littell Études réunies par Murielle Lucie Clément - Lucie Clément, Murielle (Open Book Publishers, 2010)
Les Bienveillantes (The Kindly Ones), caused a literary sensation in 2006. Described as "deliberately repellent" by The New York Times, Jonathan Littell's novel tells the story of World War II through the eyes of former SS officer Maximilien Aue. This is the first academic study of this controversial, best-selling work.Twenty-one leading scholars discuss the aesthetics, themes and characters of the novel, as well as formal aspects of Littell's writing. They tackle ideas surrounding parricide, genocide, ant-Semitism and the Holocaust as well as Littell's portrayal of both historical and fictional characters. The collection offers a deeply varied range of approaches to Littell's work and is essential reading for anyone interested in representations of World War II, the Holocaust and contemporary French literature. All the essays in this collection are written in French.